Associação entre variação de glicemia e resposta ao tratamento em pacientes com câncer colorretal estádios III E IV - SARRAF, Jonathan Souza (2018)
Serum glucose high levels are commonly associated a bad clinical prognosis in many diseases, including colorectal cancer (CRC) However, it is unknown the real impact of glucose variation (GV) on the treatment and prognosis of CRC patients. Through the absence of information, this study aimed correlate GV and treatment response in advanced CRC. 38 CRC people stage III and IV first compound this study, which were selected only who has two consecutive computed-tomography scan and more one SG among on the CT-Scans, remaining 19 people. The mean age of 19 analyzed subjects was 58.6 years sd=18.26; CI 95% 50.9 – 71.0). Most of the patients were men (59%), with Wilt-Type KRAS mutation (63,2%), without metastasis (71%) and in clinical stage III (73,3%). No statistically significant value was found (p=0.126) between GV and treatment response in advanced CRC patients. These findings cannot indicate a direct association between GV and treatment response in advanced CRC patient, but opens space for evaluate new methods of handling glucose variations, in attempt to get a better understanding about how the glucose may influence the CRC prognosis.